EXPLORE THE CONCEPT AUTHENTICITY OF HADITH THOUGHT PERSPECTIVE NABIA ABBOTT TURKEY - Kurniawan, Muh. Ilham (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
Judging from its origin, the meaning of the word orientalism has narrowed its object and is understood as a study of Islam carried out by Westerners including customs, culture, language and literature, especially Islamic studies in the East. Around the 19th-20th centuries various issues regarding the authenticity of Hadith began to emerge, including at that time there was widespread study of orientalist figures regarding the status of Hadith. The orientalists doubted the Hadith because it was judged that the codification process took a long time from the events of its transmission. The study of Hadith in the eyes of orientalists was very popular at the time, this was evidenced by the many orientalist writings that took part in this study, including Ignaz Goldziher, Joseph Schact, Juyn Boll, Harald Motzki and Nabia Abbott. The urgency of the study of the Prophet's Hadith has also been explained by Shuyudi Ismail. First, strengthen the belief that the Prophet's Hadith is the source of Islamic law. Second, emphasizing that not all of the Prophet's Hadith written at the time of the Prophet were still alive. The study conducted by the orientalists focused on research on the development of Hadith literature which used several methods to find evidence of doubts about the Hadith of the Prophet SAW. This was also done by Nabia Abbott who paid attention to the study of Hadith and at the same time became the author's discourse to explore how her thoughts and what needed to be clarified regarding the criticisms made by Nabia Abbott about Hadith with a comparison of opinions from Muslim scholars so that the discussion in this paper finds a point. clear the errors and doubts of the orientalists regarding the authenticity of the Prophet's Hadith.